Intercultural capability: exploring first year HE students' reflections on and experiences of their higher education experience - Mullen, Emma; Eccles, Sue; Dippold, Doris; Bridges, Stephanie (2016)
This round table discussion presents the initial stages of a cross-institution project exploring the reflections and expectations of first year international and home students. This study aims to capture students' early experiences in higher education (HE), their sense of 'belonging' and development of intercultural capabilities embedded in international-home student interactions. This is the first study to adopt Sen's (1992) 'capability approach' as a means of framing exploration of these intercultural capabilities. Results are intended to shed light on the processual development of intercultural capabilities during students' first year in HE, and their perceptions of how these contribute to their employability. Although this discussion is based on one joint proposal developed by the research team, several themes emerge which may be of interest to HE academics and practitioners concerning 'Student Experiences', 'Employability, Enterprise and Graduate Careers' and 'Learning, Teaching and Assessment'.